Improving civilian medical response to chemical or biological terrorist incidents : interim report on current capabilities (National Academy Press, 1998)
This interim report focuses on current civilian capabilities rather than ongoing and planned research and development (R & D) programs, which will be addressed in the committee's final report. The interim report thus provides a baseline against which to evaluate the utility of technology and R & D programs. It identifies some general areas in which innovative R & D is clearly needed, and in some cases already underway. Assessment of this work and its applicability to coping with domestic terrorism with constitute the second half of this study and be the focus of the final report.